1990
DOI: 10.1007/bf01957699
|View full text |Cite
|
Sign up to set email alerts
|

Very early prolonged premature rupture of membranes and survival

Abstract: Fetal survival is possible even with very premature rupture of membranes followed by persisting oligohydramnios, secondary Potter facies and limb deformities. A case history is given with continuous amniotic fluid loss starting at 11+4 weeks, without development of pulmonary hypoplasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…Overall these individuals have done surprisingly well in view of previous reports of oligohydramnios with and without renal anomalies (see Tables and ) [Nimrod et al, ; Mercer and Brown, ; Hoekstra & de Boer, ; Rotschild et al, ; Tibboel et al, ; McIntosh and Harrison, ]. In addition, they are reasonably well grown, which appears to be true of most cases of oligohydramnios on a non‐renal basis.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Overall these individuals have done surprisingly well in view of previous reports of oligohydramnios with and without renal anomalies (see Tables and ) [Nimrod et al, ; Mercer and Brown, ; Hoekstra & de Boer, ; Rotschild et al, ; Tibboel et al, ; McIntosh and Harrison, ]. In addition, they are reasonably well grown, which appears to be true of most cases of oligohydramnios on a non‐renal basis.…”
Section: Discussionsupporting
confidence: 59%
“…The good news in those individuals who seem to have their contractures on the basis of oligohydramnios is, that if they survive pulmonary hypoplasia, and have no central nervous system defect (70%), they seem to do quite well [Hoekstra and de Boer, ].…”
Section: Discussionmentioning
confidence: 99%
“…In all studies both neonatal mortality and/or lung hypoplasia were found to correlate positively with the degree of oligohydramnios (defined by ultrasound), earlier gestational age on admission and delivery. 6,[13][14][15][17][18][19] In the early 1990s, there were significant changes in the standards of perinatal care, including use of antenatal steroids in cases of P-PROM, use of antenatal prophylactic antibiotics, technical advances in neonatal respiratory support, and use of surfactant. In the light of these changes, we carried out a ''re-analysis'' of the literature (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the inhalation of NO decreases pulmonary vascular resistance and intrapulmonary shunting due to regional atelectasis and hyaline membrane formation associated with RDS. Infants with DLS had similar clinical findings, with an early onset of oligohydramnios due to prolonged rupture of membranes and pulmonary insufficiency requiring high ventilatory pressures 13,14 . Most of these cases received inhaled NO during high‐frequency oscillatory ventilation and showed good responses to the treatment.…”
Section: Discussionmentioning
confidence: 90%